Empirically Derived Dietary Patterns and Hypertension Likelihood: A Meta-Analysis - Cui-Jiang Wang; You-Xia Shen; Yun Liu (Kidney & Blood Pressure Research, 2016)
Background/Aims: Dietary patterns, which represent whole-diet and a complex integration of food and nutrient, have been reported to play an important role in the development of hypertension. However, the results have yielded conflicting findings. Herein, we performed this meta-analysis to evaluate the associations between different dietary patterns and the likelihood of hypertension. Methods: MEDLINE and EBSCO were searched to identify relevant articles published until the end of March 2016. A random-effects model was used to account for possible heterogeneity between studies.A total of twenty-seven studies met the inclusion criteria and were included in this meta-analysis. Results: There was evidence of a decreased likelihood for hypertension in the highest compared with the lowest categories of healthy pattern (odds ratio (OR)=0.81; 95% confidence interval(CI): 0.67-0.97; P=0.02). An increased likelihood of hypertension was shown for the highest compared with the lowest category of heavy drinking pattern (OR=1.62; 95% CI: 1.16-2.26; P=0.004), whereas no statistically significant association with western-style and light-moderate drinking pattern were observed(OR=1.04, 95% CI: 0.83-1.31; OR=1.20, 95% CI:0.94- 1.53; P>0.05). Conclusions: Our results of this systematic review and meta-analysis suggest that dietary pattern may be associated with the likelihood of hypertension.